Zakat, Infak, dan Sedekah: Modal dan Model Ideal Pembangunan Ekonomi dan Keuangan Modern - Suma, Muhammad Amin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
Zakat is the designation for a particular property that intentionally released to be channeled to mustahiq. Other financial types that always accompanies or included with it are zakat, infak and sedekah. ZIS funds can be considered as a triad of economic resources and short-term Islamic finance in synergy with other funding sources, such as grants, wills, and endowments-oriented for long-term interests. In addition to its management structure and mechanism is relatively simple and efficient, zakâh can be said always completely ready to cope with urgent needs. ZIS funds in enforceability of all peoples and Muslim nations showed that zakâh system appropriate to be used as capital and financial economic model and the most modern of all time.DOI: 10.15408/aiq.v5i2.2568